HOUSEHOLD WASTE POLLUTION AS A DILEMMA IN SOCIETY - Sumarno; Ismaidar; Arda Gerdana Purba (International Journal of Society and Law, 2025)
Household waste pollution is an environmental issue that continues to escalate and has become a social dilemma at the community level. Based on Article 67 of Law Number 32 of 2009 concerning Environmental Protection and Management, “Every person is obligated to preserve the sustainability of environmental functions and control pollution and/or environmental damage.” Each individual bears responsibility for maintaining environmental sustainability and is prohibited from engaging in actions that may degrade environmental quality. However, empirical conditions show that public awareness regarding domestic waste management remains low. Liquid waste generated from washing, bathing, detergent use, and household chemicals is often discharged directly into water bodies without prior treatment, causing water quality degradation, foul odors, and ecological imbalance. This situation creates a dilemma as society perceives such practices as normal due to limited knowledge, inadequate waste treatment facilities, and weak environmental oversight. There is also a disparity between legal norms such as Article 70 of Law Number 32 of 2009, which states that “the public has equal rights and opportunities to actively participate in environmental protection and management” and social behavior, demonstrating a significant gap in environmental policy implementation. Therefore, strategic efforts are required through environmental education, the provision of household-scale waste treatment systems, strengthened community participation, and sustainable law enforcement.